Intense endoplasmic reticulum stress (ERS) / IRE1α enhanced Oxaliplatin efficacy by decreased ABCC10 in colorectal cancer cells - Xiaohui Liu; Bo Wu; Hong Chen; Haimei Sun; Xiaoxia Guo; Tingyi Sun; Deshan Zhou; Shu Yang (BMC Cancer, 2022)
Abstract Background Attenuated Oxaliplatin efficacy is a challenge in treating colorectal cancer (CRC) patients, contributory to the failure in chemotherapy and the risks in relapse and metastasis. However, the mechanism of Oxaliplatin de-efficacy during CRC treatment has not been completely elucidated. Methods Microarray screening, western blot and qPCR on clinic CRC samples were conducted to select the target gene ABCC10 transporter. The Cancer Genome Atlas data was analyzed to figure out the correlation between the clinical manifestation and ABCC10 expression. ABCC10 knock-down in CRC cells was conducted to identify its role in the Oxaliplatin resistance. Cell counting kit-8 assay was conducted to identify the CRC cell viability and Oxaliplatin IC50. Flow cytometry was conducted to detect the cell apoptosis exposed to Oxaliplatin. The intracellular Oxaliplatin accumulation was measured by ultra-high performance liquid chromatography coupled to tandem mass spectrometry. Results CRC patients with higher ABCC10 were prone to relapse and metastasis. Differential ABCC10 expression in multiple CRC cell lines revealed a strong positive correlation between ABCC10 expression level and decreased Oxaliplatin response. In ABCC10 knock-down CRC cells the Oxaliplatin sensitivity was evidently elevated due to an increase of intracellular Oxaliplatin accumulation resulted from the diminished drug efflux. To explore a strategy to block ABCC10 in CRC cells, we paid a special interest in the endoplasmic reticulum stress (ERS) / unfolded protein response (UPR) that plays a dual role in tumor development. We found that neither the inhibition of ERS nor the induction of mild ERS had anti-CRC effect. However, the CRC cell viability was profoundly decreased and the pro-apoptotic factor CHOP and apoptosis were increased by the induction of intense ERS. Significantly, the Oxaliplatin sensitivity of CRC cells was enhanced in response to the intense ERS, which was blocked by inhibiting IRE1α branch of UPR. Finally, we figured out that the intense ERS down-regulated ABCC10 expression via regulated IRE1-dependent decay activity. Conclusion Oxaliplatin was a substrate of ABCC10 efflux transporter. The intense ERS/IRE1α enhanced Oxaliplatin efficacy through down-regulating ABCC10 in addition to inducing CHOP. We suggested that introduction of intense ERS/UPR could be a promising strategy to restore chemo-sensitivity when used in combination with Oxaliplatin or other chemotherapeutic drugs pumped out by ABCC10.